Negara Kesejahteraan (Welfare State): Mengembalikan Peran Negara Dalam Pembangunan Kesejahteraan Sosial di Indonesia - Eddy Kiswanto (Magister Ilmu Administrasi Publik, 2005)
This paper aims to study the system of social security in Indonesia. Social security represents the elementary rights of every citizen which is guaranteed by the state, like in section 27 article 2 UUD ' 45 and the laws of System of Social Security National (SJSN). Practically, the social security and social services prggram run by government framework not yet clearly with asocial policy which should be integral and continual Government has been trapped in current of liberalism and capitalism so that state role becomes progressively minimize. From 95 million labor force only 24,6 million obtain to get the social security, or newly 12% from resident amount. To overcome the weakness, resistance, and barricade in execution of social security Drstem in Indonesia, National Social Security needed to embrace the principle of government–bodies, deputizing stakeholders in this case competitor! worker, and government. Gathering and fee organizer require to be supported by openness, carefulness, accountability, and eficien. Entangling of various kind of stakeholders actor of vital importance as principal applying form of governance, the model executed by Indonesian government according should be to its society characteristic. Though financing system conducted by sharing across population, the government remain involved in the goodness in arrangement, observation, and also its financing.